UPAYA MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) DALAM MENINGKATKAN MINAT BELAJAR MATEMATIKA SISWA - Fatimah, Fety; Nani Mediatati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
In accordance with the research problem that has been formulated, the aim of this research is to find out how much interest in learning mathematics in class IV students at SD Negeri Kalicacing 02 Salatiga has increased after implementing the TGT type cooperative learning model. The hypothesis in this research is "There is an increase in students' interest in learning mathematics subjects in implementing the Teams Games Tournament (TGT) type cooperative learning model in class IV of SD Negeri Kalicacing 02, Salatiga." This research was carried out at SD Negeri Kalicacing 02 Salatiga which is located on JL. Lmu Adisucipto No.06, Rt 1 Rw. 2, Kalicacing, District. Sidomukti, Salatiga City, Central Java, in the second semester. The subjects of this research were fourth grade students at SD Negeri Kalicacing 02 Salatiga. This type of research is Classroom Action Research (PTK). Based on table 3, namely before the implementation of the Team Games Tournament (TGT) type cooperative learning model or pre-cycle, students' interest in learning obtained an average percentage of 53.38%. In cycle I, the implementation of the Team Games Tournament (TGT) type cooperative learning model experienced an increase in student interest in learning. The results of this cycle I action obtained an average percentage of 64.26%. The results of the actions in cycle II also saw an increase in students' interest in learning mathematics. The average percentage gain is 79.19%. The results of this classroom action research show that the Teams Games Tournament (TGT) cooperative learning model is suitable for application in mathematics subjects for fourth grade students at Kalicaing 02 State Elementary School as a solution to the problem of low interest in learning mathematics. Based on the results of research that has been carried out, it is concluded that the Teams Games Tournament (TGT) cooperative learning model can increase interest in learning mathematics in class IV students at SD Negeri Kalicacing 02 in the 2023/2024 academic year. This increase can be seen from the increase in students' interest in learning from  Cycle I to Cycle II.